HUBUNGAN BUDAYA KESEHATAN DAN KESELAMATAN KERJA (K3) TERHADAP PRODUKTIVITAS KERJA DI BAGIAN INSTALASI PG.MRITJAN KEDIRI - Ratna Wardhani; Edvin Ardiantoko; Amarin Yudhana (Universitas STRADA Indonesia, 2013)
One of the company’s goal is to increase the productivity of the company. The purpose of this research is to know the relationship of occupational health and safety culture on labor productivity in the section Installation of PG.Mritjan kediri.The research uses cross sectional design. Population is all the workers in worker of Installation PG.Mritjan kediri using total sampling technique, a total sample of 59 respondents.The results of this research on variable occupational health and safety culture (K3) shows that 32 respondents (54,2%) were able to implement a culture of safety and occupational health well and on labor productivity got 54 respondents or (91,5%) had Good work productivity. Using Correlation pearson analysis, the level of significance value = 0,000 ( = 0,05) showed occupational health and safety culture on the productivity of labor in the section Installation PG.Mritjan Kediri. This is because the company provides health insurance, fulfillment of personal protective equipment and to provide job training to workers so as to improve quality and efficiency in work.